Theoretical and experimental analysis of radiative recombination lifetimes in nonpolar InGaN/GaN quantum dots - Kanta Patra, S; Wang, T; Puchtler, T; Zhu, T; Oliver, R; Taylor, R; Schulz, S (Wiley, 2017)
We present here a combined experimental and theoretical analysis of the radiative recombination lifetime in a-plane (11 (Formula presented.) 0) InGaN/GaN quantum dots. The structures have been grown by modified droplet epitaxy and time-resolved photoluminescence measurements have been performed to gain insight into the radiative lifetimes of these structures. This analysis is complemented by multi-band k·p calculations. To account for excitonic effects, the k·p theory is coupled with self-consistent Hartree calculations. Special attention is paid to the impact of the quantum dot size on the results. Our calculations show that the residual built-in fields in these nonpolar structures are compensated by the attractive Coulomb interaction, leading to the situation that the oscillator strength is almost unaffected by changes in the quantum dot size. Furthermore, our theoretical studies reveal that the radiative lifetimes are one order magnitude lower than values for c-plane systems of identical size and shape. Our theoretical findings are consistent with experimental results. Also, the calculated lifetimes are comparable in ma gnitude to the measured values. The majority of the measured dots produce lifetime values of 250–300 ps, highlighting the potential of these nanostructures for future high-speed single-photon emitters.